Pengembangan Metode Pembelajaran Kitab Kuning Dalam Mencetak Ahli Fiqh - Rusdi, Rusdi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
The yellow book is a valuable source of knowledge for mankind, since many Muslim figures have written their works in the form of yellow book, yellow book methodology as a vehicle for channeling and studying the works of the 'ulama' and Muslim scholars conducted by pesantren very both for the development of thought and morals of the successors of Islam in the future. Thus this effort can be concluded about the development of yellow book method of learning in printing Fiqh experts, where in the development of yellow book methodology in printing Fiqh experts include several things such as using varied methods and models by combining pesantren learning model with a college model.